Conventional and Microwave-Assisted Synthesis of 4’-Bromochalchone Utilizing 4-Bromoacetophenone and Benzaldehyde as Starting Material in Alkaline Condition - Iin Narwanti; Hanna Nur Aisyah Afifah (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
This study focuses on synthesizing 4’-bromochalcone through conventional and irradiation microwave methods to determine each method's time efficiency and yield. 4-Bromoacetophenone was treated with benzaldehyde in the presence of a base. Conventionally, the reaction mixture was stirred at room temperature. While in the microwave irradiation method, the reaction mixture was irradiated at a power of 140 watts. The compound was identified, including the melting point and physicochemical properties. The structure of the compound was confirmed by infrared, 1H- and 13C-nuclear magnetic resonance, and mass spectroscopy spectral data. The results showed that 4’-bromochalcone had been successfully synthesized using conventional and microwave irradiation methods in a good yield (94.61%±0.6793 and 89.39%±0.6418, consecutively). The structure assignment based on infrared, 1H- and 13C-nuclear magnetic resonance, and mass spectroscopy spectral data revealed that the synthesized product was 4’-bromochalcone. Synthesis of 4’-bromochalchone using microwave irradiation could be done in a shorter time than the conventional method.